2005
DOI: 10.1097/01.inf.0000168755.01196.49
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Metapneumovirus From Children With Acute Otitis Media

Abstract: Nasal and middle ear specimens collected from children with acute otitis media were subjected to viral isolation and bacteria culture. All virus-negative specimens underwent reverse transcription polymerase chain reaction to detect human metapneumovirus. Three of 126 middle ear specimens were positive by this assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
2
17
0
3
Order By: Relevance
“…Complications of AOM can be severe and require hospitalization or surgical intervention [17]. Our study adds to the two previous reports on hMPV and AOM [18,19]. The detection of hMPV in 1/144 MEF does not definitively establish a direct role for hMPV in middle ear pathogenesis.…”
Section: Discussionmentioning
confidence: 34%
“…Complications of AOM can be severe and require hospitalization or surgical intervention [17]. Our study adds to the two previous reports on hMPV and AOM [18,19]. The detection of hMPV in 1/144 MEF does not definitively establish a direct role for hMPV in middle ear pathogenesis.…”
Section: Discussionmentioning
confidence: 34%
“…Further studies are needed to clarify the importance of antigenic variation of HMPV in human populations with respect to the clinical course of infection. HMPV is associated with acute otitis media, and viral RNA can be detected in middle ear fluid (199,217,252).…”
Section: Symptoms and Pathologymentioning
confidence: 99%
“…It has been shown that 30 to 85% of children hospitalized with HMPV have chronic conditions, such as asthma, chronic lung disease due to prematurity, congenital heart disease, or cancer (29,63,72,168,173,225,234). Hospitalization of adults or children for HMPV-associated lower respiratory tract infections is more likely for patients with underlying conditions such as asthma, chronic obstructive pulmonary disease (COPD), HIV infection, immunocompromised status, or prematurity (34,66,75,78,106,122,163,168,187,193,217,229,242,253,254).…”
Section: Risk Groups Other Than Childrenmentioning
confidence: 99%
“…However, the role of hBOV as a causative URI pathogen has been debated (3,23,25). Human metapneumovirus (hMPV), described in 2001 (32), also has been isolated from middle ear fluid samples from children with AOM (29,31). Retrospective analyses indicated that more than half of URI episodes due to hMPV were complicated by AOM (35).…”
mentioning
confidence: 99%